Histological Study of Splenic Capsule in Bangladeshi Cadaver (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: Thickness of splenic capsule shows positive correlation with age. The capsule and trabeculae of the spleen consist of dense collagenous connective tissue with some elastic fibers and smooth muscle fibers. Objective: To find out the histomorphic changes of splenic capsule in relation to age and sex of the Bangladeshi cadaver.Methods: This cross-sectional descriptive study was carried out on 40 fresh spleens collected from the morgue of Department of Forensic Medicine of Mymensingh Medical College from July 2007 to April 2008. Collected tissue samples were stained with Haematoxylin and Eosin (H&E) stain, AZAN and Van-Gieson’s stain. The selected fields in the slides were studied and micro photographed by a special microscopic device. Collected data were analyzed statistically by the computer generated programme SPSS using ‘F’ test, ANOVA, ‘r’ test and difference among groups was determined using comparison method at 5%, 1% or 0.1% level of significance.Results: The maximum thickness of splenic capsule were 65.30, 78.54, 92.56, 95.64, 113.05µm in male and 61.50, 80.23, 98.34, 98.62, 114.20µm in female in age group A, B, C, D, E respectively. The minimum thickness were 53.00, 67.00, 72.12, 81.23, 100.50µm in male and 56.23, 61.50, 83.50, 92.80, 102.95µm in female. With the help of special staining abundant smooth muscle cells are identified in the splenic capsule and trabecule.Conclusion: Most of the splenic disease can be managed with conservation of spleen by invasive and non-invasive method. Detail knowledge on splenic capsule will help the physician to manage splenic disease.JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 51-56